Tác động của cổ phần hóa đến hiệu quả hoạt động sau cổ phần hóa của các doanh nghiệp nhà nước tại Việt Nam - Nguyễn Văn Tân; Trịnh Quốc Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This research aims to provide empirical evidence on the impact of equitization policy on firm performance of equitized state-owned enterprises (SOEs) after equitization in Vietnam. With the selection of 47 equitized SOEs in Vietnam in 2013 and 146 non-equitized SOEs over the same period based on survey data of Vietnamese General Statistics Office, the authors conclude that equitization generally does not help equitized SOEs perform better when considered in relation to non-equitized SOEs over the same period. This study is the first one combining the pre-post comparison method (through propensity score matching technique) and the weighted regression method to examine the impact of equitization on firm performance of equitized SOEs after equitization in Vietnam.